Helping in Teams - Anastasia Danilov; Christine Harbring; Bernd Irlenbusch (Institute for the Study of Labor (IZA), 2014)
We study, how help can be fostered under relative rewards by means of team bonus and corporate value statements. A simple model analysis suggests that team members help less as relative rewards increase. As one potential measure to encourage help, we augment relative rewards with team rewards determined by the output of the whole team. This theoretical benchmark is tested in an experiment. Furthermore, we provide the first clean one-shot experimental test of the Lazear and Rosen (1981) tournament model. In a second experiment, we investigate the effectiveness of corporate value statements to encourage help.
Keywords: M52; J33; J41; L23; C72; C91; 330; help; relative rewards; team incentives; corporate value statements; experiment